Demographic Profile of Poisoning Cases in a Tertiary Care Center in South India – An Observational Study - James Rajesh J1 , Sampath Kumar P2 , Priyadarshee Pradhan3, Jothi Marie Feula A4 , Siva Reddy B5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The word ‘poison’ has been evolved from the Latin word ‘potion’ i.e. ‘to drink for health’, but in the due course of time the definition of ‘poison’ has changed reversibly to its present form i.e. any substance which when administered, inhaled or ingested is capable of acting deleteriously on the human body. In the current study we have aimed at determining the demographic profile of poison cases reporting to our institute. This prospective study was carried out involving 353 cases of poisoning admitted in Sri Ramachandra Medical College & Research Institute, Sri Ramachandra University, Porur, Chennai, during the period of June 2014- June 2015. Age-wise distribution of poisoning cases revealed that the maximum cases are in the age group of 20-29 years and the incidence decreased as the age increases. It is evident that the incidence of poisoning is more in case of females when compared to males. Occupation-wise distribution revealed poisoning is more common among people who are skilled workers contributing 167 cases. Socio economic status wise distribution revealed poisoning is more common among the people who belong to Upper middle (52%), followed by 33% of cases belong to Middle class. Poisoning is more common among married people when compared to unmarried people. Out of 353 cases, 203 cases were married, which accounts for 58%, 150 cases were unmarried, which accounts for 48%. Distribution of the study population based on the type of family revealed that out of total 353 cases, 299 cases belonged to nuclear family. Persons who belong to joint family were 46 in number.